PARTISIPASI POLITIK PEREMPUAN DALAM PEMILIHAN KEPALA DAEARAH RIAU TAHUN 2013 ( STUDI KASUS DI KELURAHAN BATANG SEROSA KECAMATAN MANDAU KABUPATEN BENGKALIS) - ", Susanti; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the factors that influence women's political participation in elections candidates for Governor and candidate for Vice Governor of Riau in 2013 in the village of Batang serous, research was conducted in the village of Batang Serous Mandau sub Bengkalis. This study used a descriptive quantitative method by using data retrieval women enrolled in the DPT in Sub Trunk serous, to know clearly what factors affect the political participation of women in the village Trunk Serous. To collect the data of the respondents used the method of direct observation, interviews, documentation, questionnaire and for the management of data used descriptive quantitative method. The government has also sought to increase the political participation of women in all respects, especially in using the right voice or sound pencbolosan. The results of this study are bahwasannya women in Sub Trunk Serous in his political participation is less political participation, especially when using the voting rights in the election of Governor and Deputy Governor of Riau in 2013, the lack of women's political participation in the election of regional heads is caused by various factors, especially Election Commission Mandau sub Less socialize procedures in elections daearhnya. So that makes women obstructed and do not know the procedures in the correct use of their voting rights.Keywords : Political Participation , Women , General Election.